Penerapan Token Ekonomi untuk Meningkatkan Motivasi Belajar dan Kedisiplinan Siswa Kelas 9 SMP - Muhammad Jamaluddin; Shaafiyah Santi Azzahra; Dimas Rangga Aditya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effectiveness of the token economy method inimproving learning motivation and discipline among 9th-grade students at SMPPGRI Jabung. The research employed a quantitative experimental approach witha one-group pretest-posttest design. The subjects consisted of five randomlyselected students using a random sampling technique. The instruments usedincluded a learning motivation and discipline scale, daily observation sheets, tokencards, and student reflections. The intervention was conducted over seven daysthrough the implementation of a token economy system. The results showed thatfour out of five students experienced an increase in their posttest scores, whileone student showed a decline. The average pretest score was 50.2, whichincreased to 52.4 in the posttest, resulting in a mean difference of +2.2 points. Incomparison, the simulated control class experienced a decrease in the averagescore from 50.0 to 49.6. These findings indicate that the token economy methodhas a positive influence on enhancing students' learning enthusiasm anddiscipline, although individual responses to the method may vary. Therefore, tokeneconomy can be considered an alternative strategy for fostering more motivatedand disciplined learning behavior, particularly during the transitional phase ofadolescence.